Pain in the Prehospital Setting in Rwanda: Results of a Mixed-Methods Quality Improvement Project. (18th September 2020) - Rosenberg, A.; Uwitonze, E.; Dworkin, M.; Guidry, J. P. D.; Cyuzuzo, T.; Banerjee, D.; McIntyre, K.; Carlyle, K.; Uwitonze, J. M.; Kabagema, I.; Dushime, T.; Jayaraman, S.
Abstract : Introduction . Pain is a universal human experience tied to an individual's health but difficult to understand. It is especially important in health emergencies. We performed a two-step quality improvement project to assess pain management by the SAMU ambulance service in Kigali, Rwanda, examining how pain is assessed and treated by ambulance staff to facilitate development of standardized guidelines of pain management in the prehospital setting, which did not exist at the time of the study. Materials and Methods . Deidentified ambulance service records from December 2012 to May 2016 were analyzed descriptively for patient demographics, emergency conditions, pain assessment, and medications given. Then, anonymized, semistructured interviews of ambulance staff were conducted until thematic saturation was achieved. Data were analyzed using a grounded theory approach. Results . SAMU managed 11, 161 patients over the study period, of which 6, 168 (55%) were documented as reporting pain and 5, 010 (45%) received pain medications. Men had greater odds of receiving pain medications compared to women (OR = 3.8, 95% CI (3.5, 4.1), p  < 0.01). Twenty interviews were conducted with SAMU staff. They indicated that patients communicate pain in different ways. They reported using informal ways to measure pain or a standardized granular numeric scale. The SAMU team reviewed these results and developed plans to modify practices. Conclusions . We reviewed the existing quality of pain management in the prehospital setting in Kigali, Rwanda, assessed the SAMU staff's perceptions of pain, and facilitated standardization of prehospital pain management through context-specific guidelines.